2013
DOI: 10.1007/s00296-013-2680-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in patients with systemic sclerosis: relationship between the clinical variables, depressive symptoms, functional status, and the quality of life

Abstract: The aim of this study is to evaluate the relationship between the sleep quality and the disease-related variables, functional status, quality of life, and depressive symptoms in patients with systemic sclerosis (SSc). Forty-eight patients diagnosed with SSc and 42 healthy control subjects were enrolled in the study. The demographic and clinical characteristics of the patients such as the Raynaud's phenomenon, SSc subtype, digital ulcers, gastrointestinal and lung involvement, and disease activity were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
4
14
2
Order By: Relevance
“…It has been reported that many chronic painful conditions and rheumatic diseases are related to poor sleep quality. 18,19 We also found higher frequency of poor sleep quality in acne patients than in healthy controls. Menstrual cycle is related to the presence of sleep disturbances and many women experience a worsening of acne during the premenstrual cycle.…”
Section: Discussionsupporting
confidence: 51%
“…It has been reported that many chronic painful conditions and rheumatic diseases are related to poor sleep quality. 18,19 We also found higher frequency of poor sleep quality in acne patients than in healthy controls. Menstrual cycle is related to the presence of sleep disturbances and many women experience a worsening of acne during the premenstrual cycle.…”
Section: Discussionsupporting
confidence: 51%
“…Studies with healthy participants have demonstrated that poor sleep quality and experimentally-induced sleep restriction are associated with higher pain ratings and hyperalgesia in response to an evoked pain sensitivity paradigm (5, 21). Further, there is some evidence suggesting that the stress response system or HPA axis functioning may mediate the relationship between sleep quality and evoked pain (21). …”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in the literature evaluating sleep quality in patients with SSc. 18,19 Sariyildiz et al, 19 evaluated sleep quality using the Pittsburg Sleep Quality Index (PSQI) in patients with SSc and found significantly higher scores for sleep quality, sleep latency, sleep disturbance, and total PSQI scores in the control group.…”
Section: Discussionmentioning
confidence: 99%